A Fixed Point Theorem in T- Metric Space - Süheyla Elmas (Utilitas Mathematica, 2022)
In this article, the concept of T-metric spaces will be introduced.I have present some fixed point theorems for two maps on full T-metric spaces. I have show that two unovalent mapping can be obtained in T-metric spaces using the similar method in a common fixed point theorem.